2021
DOI: 10.1186/s41256-021-00199-y
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographics and asthma prevalence, management, and outcomes among children 1–11 years of age in California

Abstract: Background Asthma disproportionately affects minority and low-income children. We examined asthma prevalence, management and outcomes, focusing on race/ethnicity and acculturation of parents (particularly English language proficiency). Methods This cross-sectional, correlational analysis used a de-identified population-based survey, the California Health Interview Survey, for years 2001–2015. Survey-weighted analysis with SAS 9.4 was used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
2
1
3
Order By: Relevance
“…This gender-related switch has been explained by many hypothesis like smaller airways in boys compared to girls [ 18 ] and increase in the activities of sex hormones in females starting from puberty [ 19 , 20 ]. AOA, as well as COA, is more prevalent among Whites in our study, which appears to be inconsistent with national data and other literature [ 1 , 21 , 22 ]. Similarly, another national-level study conducted by Keet et al concluded that the Black race and Puerto Rican ethnicity was a risk factor in developing asthma in children and a study done by Holt et al revealed that COA was higher among children of mothers who were Puerto Rican and Black than White (40.4% vs. 23.7% vs. 12.6%) [ 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This gender-related switch has been explained by many hypothesis like smaller airways in boys compared to girls [ 18 ] and increase in the activities of sex hormones in females starting from puberty [ 19 , 20 ]. AOA, as well as COA, is more prevalent among Whites in our study, which appears to be inconsistent with national data and other literature [ 1 , 21 , 22 ]. Similarly, another national-level study conducted by Keet et al concluded that the Black race and Puerto Rican ethnicity was a risk factor in developing asthma in children and a study done by Holt et al revealed that COA was higher among children of mothers who were Puerto Rican and Black than White (40.4% vs. 23.7% vs. 12.6%) [ 23 , 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This differential association underscores the interaction between genetic and nongenetic factors in the development of a disease 30 . Indeed, longitudinal studies have shown that ethnic‐related differences are present in asthma risk and its outcomes 31–33 . Ethnic‐specific analyses may therefore provide insights into the biological mechanisms of pediatric asthma in specific populations.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Indeed, longitudinal studies have shown that ethnic‐related differences are present in asthma risk and its outcomes. 31 , 32 , 33 Ethnic‐specific analyses may therefore provide insights into the biological mechanisms of pediatric asthma in specific populations. It is known that the A allele of the IL10 rs1800896 polymorphism results in lower mRNA levels of IL‐10 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Otros estudios han demostrado hallazgos similares. 16 Al respecto, existe evidencia del efecto protector de la testosterona en la respuesta inflamatoria alérgica. [17][18][19] Incluso se ha observado que el género (hombres y mujeres) puede tener participación importante para propiciar un gradiente diferente de exposición a los alérgenos.…”
Section: Discussionunclassified